Jurong island groundwater study : hydrological and hydraulic investigations - Wong, Jia Min. (2013)
With an increase in industrial growth, there is a scope to consider developing a localised water supply on Jurong Island. This project aims to carry out hydrological and hydraulic investigation of abstraction of groundwater from the unconfined sand aquifers. Firstly, an estimation of rainfall recharge using field data from pilot test conducted in 2010 is done through water-table fluctuation method. Recharge is calculated to be of minimum 29%, an average value of 50% and maximum of 62% out of the total amount of precipitation. Subsequent analyses are done based on an estimated recharge rate of 30% and 50%. Total sustainable yield is computed with an ideal assumption that all of the recharge can be abstracted gives average values of 17.6 x 10^6 m^3/year (30% recharge) and 30.1 x 10^6 m^3/year (50% recharge). The sustainable pumping rate and minimum well spacing with saltwater intrusion control are correspondingly calculated to be 2.3 l/s and 444 m respectively for an estimated recharge rate of 30% and well diameter of 2 m. Yield reliability remains relatively stable if intended withdrawal is less than approximately 40000 m^3/day (30% recharge) and 60000 m^3/day (50% recharge). In addition, open wells and radial well collectors are suitable abstraction methods. It is suggested to conduct another round of test from the start of January to end of December (12 months) with well diameter of at 2m in order to justify the outcomes in this project. Studies on methods of artificial recharge can be further looked into for yield increments. Nevertheless, effective management and protection of groundwater scheme are the keys to sustainable resource.